2004
DOI: 10.1111/j.0022-202x.2004.22308.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of the Maspin Gene Associated with Epigenetic Modification in Melanoma Cells

Abstract: Maspin, a mammary serine protease inhibitor, was originally reported to be a tumor suppressor gene in breast and prostate cancers. The expression pattern of the maspin gene differs among cancer types and normal tissue however, and its significance as a tumor suppressor has been questioned. In this study, maspin expression and/or allele-specific methylation status were investigated in five melanoma cell lines and a normal human epidermal melanocyte (NHEM) cell line, and 80 surgically resected tumors (40 melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 39 publications
3
36
2
5
Order By: Relevance
“…However, a high degree of variability was reported by different groups as for the frequency of protein expression, with maspin positivity ranging from 0 to 94% in primary tumors, and from 0 to 100% in metastases. 27,[29][30][31] Interestingly, when maspin expression was examined in clinical samples from various cancers, with tumor cells being analyzed in the context of host, stromal, and environmental influences, conflicting results were obtained, and the tumor-suppressive activity of maspin has been questioned. From these studies, it is becoming evident that not only protein expression, but also its sub-cellular localization, and consequently its putative interactors and functions, may influence its association with disease outcome and patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a high degree of variability was reported by different groups as for the frequency of protein expression, with maspin positivity ranging from 0 to 94% in primary tumors, and from 0 to 100% in metastases. 27,[29][30][31] Interestingly, when maspin expression was examined in clinical samples from various cancers, with tumor cells being analyzed in the context of host, stromal, and environmental influences, conflicting results were obtained, and the tumor-suppressive activity of maspin has been questioned. From these studies, it is becoming evident that not only protein expression, but also its sub-cellular localization, and consequently its putative interactors and functions, may influence its association with disease outcome and patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies performed on melanoma tissues did not specifically investigate the sub-cellular location of maspin, published data report the protein as nuclear, 31 mixed nuclear and cytoplasmic, 30 and purely cytoplasmic. 29 To the best of our knowledge, this is the first study aimed at specifically examining the association of maspin expression and sub-cellular localization with disease progression in a large cohort of melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that early hypermethylation of the Maspin promoter might play a role in silencing Maspin. In addition, loss of Maspin was shown to correlate with increased tumor thickness (15)(16)(17).…”
mentioning
confidence: 99%
“…Denk and colleagues found that metastatic melanoma cells had decreased expression levels of Maspin compared with normal human epidermal melanocytes (15). Moreover, Maspin expression is lost with increased tumor thickness in clinical specimens as the tumor progresses from nonmetastatic to metastatic melanoma (16,17). Previous reports have shown that early hypermethylation of the Maspin promoter might play a role in silencing Maspin.…”
mentioning
confidence: 99%